An exploration of rural transportation policies through quantitative selection of case studies - Rearick, Emma Louise (Kansas State University, 2017)
Personal automobile use is commonly recognized as impacting public health, environmental sustainability, land use, and household expense. Car use is closely tied to car ownership rates, and fewer cars per household could indicate greater utilization of alternative modes of transportation. Most car ownership and active transportation research focuses on urban areas. However, much of the United States remains rural, and different factors may impact car ownership in less-densely populated areas. This research examines car ownership trends in rural counties to identify communities with lower than expected rates of car ownership considering demographic factors. 2,285 counties in the continental United States were identified as rural according to guidelines found in the Agriculture Act of 2014. These counties were grouped into five regions based on U.S. Census Bureau definitions. To identify counties of interest, an Ordinary Least Squares regression was created for each region that incorporated data from the 1990 Decennial Census and 2014 5-year American Community Survey. Two counties from each region were selected and studied for policies that may be correlated with car ownership rates: a county with a lower-than-expected car ownership rate change and a county with a typical car ownership rate change to serve as a control. Local professionals were interviewed and relevant policies summarized.
Keywords: Rural; Automobile ownership; Transportation planning